KARAKTERISTIK PENDERITA TUBERKULOSIS PARU RELAPS YANG BEROBAT DI POLIKLINIK PARU RUMAH SAKIT UMUM DAERAH ARIFIN ACHMAD PROVINSI RIAU TAHUN 2012-2013 - Widya Syah Fitri; Sri Melati Munir; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. Most of the TB cases (95%) and death (98%) occured in developing countries. Relapse of TB are patients who previously got TB treatments, where declared cured or achieved completed treatment at the end of their most recent course of treatment, and are now diagnosed with a relapse episode of TB by sputum smear or culture results positive. This research was a descriptive retrospective study, which was conducted by using medical record of patients. Sample collected by using total sampling method. The results showed that patients relapse of pulmonary tuberculosis who undergone theraphy in lung department of RSUD Arifin Achmad showed large proportion in the age group 25-44 years (44.1%), the most gender was males (73.5%%), most work was labours (50.9%), most of patients had no history of weight gain (65.7%), time of relapse was < 4 years (80.4%), most comorbidities were no comorbidity (57.8%), most regularity of taking medicine was unregularly (66.7%), and most of patients had history of adverse effect in OAT treatment (68.6%).Key words :Tuberculosis (TB), relapse.